Symbiont type and environmental factors affect transcriptome‐wide gene expression in the coral Montipora capitata. Issue 1 (27th December 2018) - Helmkampf, Martin; Bellinger, M. Renee; Frazier, Monika; Takabayashi, Misaki
Abstract: Reef‐building corals may harbor genetically distinct lineages of endosymbiotic dinoflagellates in the genus Symbiodinium, which have been shown to affect important colony properties, including growth rates and resilience against environmental stress. However, the molecular processes underlying these differences are not well understood. In this study, we used whole transcriptome sequencing (RNA‐seq) to assess gene expression differences between 27 samples of the coral Montipora capitata predominantly hosting two different Symbiodinium types in clades C and D. The samples were further characterized by their origin from two field sites on Hawai'i Island with contrasting environmental conditions. We found that transcriptome‐wide gene expression profiles clearly separated by field site first, and symbiont clade second. With 273 differentially expressed genes (DEGs, 1.3% of all host transcripts), symbiont clade had a measurable effect on host gene expression, but the effect of field site proved almost an order of magnitude higher (1, 957 DEGs, 9.6%). According to SNP analysis, we found moderate evidence for host genetic differentiation between field sites ( F ST = 0.046) and among corals harboring alternative symbiont clades ( F ST = 0.036), suggesting that site‐related gene expression differences are likely due to a combination of local adaptation and acclimatization to environmental factors. The correlation between host gene expression and symbiont clade may be due to several factors, including host genotype or microhabitat selecting for alternative clades, host physiology responding to different symbionts, or direct modulation of host gene expression by Symbiodinium . However, the magnitude of these effects at the level of transcription was unexpectedly small considering the contribution of symbiont type to holobiont phenotype. Abstract : This study explores transcriptome‐wide gene expression patterns in the coral Montipora capitata with respect to differences in sampling location and dominant Symbiodinium clade. We found that clade had a measurable effect on host gene expression, but the effect of location proved almost an order of magnitude higher. Genes and pathways associated with these patterns are identified and discussed.